A Transdisciplinary Overlay for Nature-Based Design of Sustainable Buildings - Anosh Nadeem Butt; Branka Dimitrijević (Architecture)
The article presents the development and validation of transdisciplinary collaboration (TDC) guidelines for nature-based design (NBD) of sustainable buildings that were used to develop and validate a proposed NBD Overlay of the Royal Institute of British Architects (RIBA) Plan of Work (PoW) 2020. The study first presents the results of consultations with architects on the application of NBD in all stages the RIBA PoW. The development of the proposed NBD Overlay of the RIBA PoW is described, followed by the results of a survey of architects on its contents. Over 80% of the architects in the consultation group confirmed the significance of the proposed NBD Overlay and its relevance in advancing sustainable building practices. The potential of the proposed NBD Overlay to foster tansdisciplinary collaboration and promote NBD approaches, principles, and solutions bodes well for the future of sustainable architecture, driving the industry towards a more resilient and environmentally conscious built environment.